2009
DOI: 10.1016/j.jfa.2008.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Structure of derivations on various algebras of measurable operators for type I von Neumann algebras

Abstract: Given a von Neumann algebra M denote by S(M) and LS(M) respectively the algebras of all measurable and locally measurable operators affiliated with M. For a faithful normal semi-finite trace τ on M let S(M, τ ) be the algebra of all τ -measurable operators from S(M). We give a complete description of all derivations on the above algebras of operators in the case of type I von Neumann algebra M. In particular, we prove that if M is of type I ∞ then every derivation on LS(M) (resp. S(M) and S(M, τ )) is inner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
77
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 17 publications
(59 reference statements)
4
77
0
3
Order By: Relevance
“…we obtain a linear operator D δ on M n (S(Z, τ Z )), which is a derivation on the algebra M n (S(Z, τ Z )) (see [2]). Now if M is an arbitrary finite von Neumann algebra of type I with the center Z, then there exists a family {z n } n∈F , F ⊆ N, of orthogonal central projections in M such that sup n∈F z n = 1 and M is * -isomorphic to the C * -product of homogeneous von Neumann algebras z n M of type I n respectively, n ∈ F, i.e.…”
Section: ) Is a Derivation On S(m τ) In Particular Any T τ -Continmentioning
confidence: 99%
See 1 more Smart Citation
“…we obtain a linear operator D δ on M n (S(Z, τ Z )), which is a derivation on the algebra M n (S(Z, τ Z )) (see [2]). Now if M is an arbitrary finite von Neumann algebra of type I with the center Z, then there exists a family {z n } n∈F , F ⊆ N, of orthogonal central projections in M such that sup n∈F z n = 1 and M is * -isomorphic to the C * -product of homogeneous von Neumann algebras z n M of type I n respectively, n ∈ F, i.e.…”
Section: ) Is a Derivation On S(m τ) In Particular Any T τ -Continmentioning
confidence: 99%
“…We have conjectured in [1,2] that the existence of such "exotic" examples of derivations is closely connected with the commutative nature of these algebras. This was confirmed for the particular case of type I von Neumann algebras in [1,2], moreover we have investigated and completely described derivations on the algebra LS(M) of all locally measurable operators affiliated with a type I von Neumann algebra M and on its various subalgebras. Recently the above conjecture was also confirmed for the type I case in the paper [6] by a representation of measurable operators as operator valued functions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some properties of cyclically compact operators on Hilbert-Kaplansky modules have been investigated in [7,8]. Certain natural applications of Hilbert-Kaplansky modules appeared in [1]. Namely, it has been shown that the algebra of all locally measurable operators with respect to a type I von Neumann algebra can be represented as an algebra of all bounded module-linear operators acting on a Hilbert-Kaplansky module over the ring of measurable function on a measure space.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, it has been shown that the algebra of all locally measurable operators with respect to a type I von Neumann algebra can be represented as an algebra of all bounded module-linear operators acting on a Hilbert-Kaplansky module over the ring of measurable function on a measure space. This result played a crucial role in the description of derivations on algebras of locally measurable operators with respect to type I von Neumann algebras and their subalgebras (see for example, [1][2][3][4]). …”
Section: Introductionmentioning
confidence: 99%
“…В случае, когда ℳ коммутативная * -алгебра, критерием существования ненулевых дифференцирований в (ℳ) служит отсутствие свойства -дистрибутивности у булевой алгебры проекторов из ℳ [5]. Для алгебры фон Ней-мана ℳ типа задачи описания дифференцирований в алгебрах (ℳ) всех изме-римых, (ℳ, ) всех -измеримых и (ℳ) всех локально измеримых операторов решены в работах [6] и [7]. В частности, для алгебр фон Неймана ℳ типа ∞ уста-новлено, что любое дифференцирование на алгебрах (ℳ), (ℳ, ), (ℳ) явля-ется внутренним.…”
unclassified